Agronomic performance of cocoa production type systems in Colombia - Héctor Eduardo Hernández-Núñez; Juan Carlos Suárez; Hernán J. Andrade; Angie Paola Bernal Núñez; David Ricardo Gutiérrez; Gustavo Adolfo Gutiérrez; Isabel Gutiérrez-Montes; V. Ernesto Méndez; Fernando Casanoves (PLoS ONE, 2025)
Socio-economic and livelihood conditions influence the design of cocoa-based agroforestry systems (AFS), as they determine the selection of accompanying species and the overall productivity of the system. These arrangements contribute to income diversification, enhanced food security and increased resilience to climate-related impacts. However, achieving these benefits depends to a large extent on the capabilities of rural households, which are shaped by their human, social, cultural, political, financial, natural, and infrastructural assets. This study analyzes the incidence of rural household type, according to livelihood strategies on the agronomic performance and co-product generation of cocoa crops established in agroforestry systems, in the departments of Caquetá, Huila and Meta in Colombia. Capital endowments for cocoa production, as well as the intensity and frequency of shade canopy species associated with cocoa, were determined in 83 rural households. Then, 112 sampling plots of 1000 m 2 were established, where 20 variables of information on floristic composition, forest structure of the AFS, state of pest attack and diseases, and cocoa bean production were taken. It was found that the agroforestry characteristics of the cocoa crop and its production differed between rural household types and departments. A total of 176 species associated with cocoa were found, but only 89 were recognized by the farmers. These species were grouped into 17 uses, the most frequent being self-consumption, shade, wood, and sale (for human food). The livelihood strategy and assets for cocoa production had a high impact on the agronomic performance of the crop. Households with more experience, technology, knowledge and dedication to the crop obtained higher cocoa bean yields. These results affirm that the management and efficiency of cocoa-based AFS depend on the articulation of social processes and the design of the AFS.